Incidence and prognostic value of acute kidney injury in pulmonary embolism: data from the SIRENA registry - M. V. Menzorov; V. V. Filimonova; A. D. Erlikh; O. L. Barbarash; S. A. Berns; E. A. Shmidt; D. V. Duplyakov (Российский кардиологический журнал, 2022)
Aim. To evaluate the incidence and severity of acute kidney injury (AKI), as well as its ability to reclassify the risk of premature mortality and association with inhospital mortality in patients with pulmonary embolism (PE) in the Russian population.Material and methods. From April 2018 to April 2019, the SIRENA Russian Multicenter Registry included patients with PE, as well as the deceased, in whom the PE was detected by autopsy. AKI was diagnosed according to current KDIGO guidelines (2012). Creatinine calculated according to the MDRD equation and corresponding to a glomerular filtration rate of 75 ml/min/1,73 m2 (baseline) was taken as the initial one, with subsequent assessment relative to the parameter value upon admission. The risk stratification of early death was carried out in accordance with the current ESC clinical guidelines (2019).Results. A total of 604 patients with PE were examined (men — 293 (49%), women — 311 (51%), mean age — 64±15 years). AKI was diagnosed in 223 (37%) of them. Stage 1 AKI was detected in 146 (65%), 2 — in 55 (25%), 3 — in 22 (10%) patients. Prior chronic kidney disease was recorded in 61 (10%) patients. Seventy-one (12%) patients had a high risk of death, 364 (61%) — intermediate risk, and 164 (27%) — low risk. The AKI incidence increased as the severity of PE increased: at low risk of death — 26%, intermediate — 38%, high — 59% (p<0,0001). In total, 107 (18%) patients died in the hospital. AKI led to an increase in mortality within following risk groups: at low risk, this effect was a trend (6 (5%) vs 6 (14%); p=0,052); at intermediate and high risk, significant differences was obtained (30 (13%) vs 41 (30%), p<0,001; 4 (14%) vs 19 (45%), p=0,006, respectively). Multivariate Cox regression demonstrated that AKI is a predictor of inhospital death (odds ratio (OR), 3,66 (95% confidence interval (CI): 2,37-5,66; p<0,0001), regardless of increased troponin levels (OR, 1,31 (95% CI: 0,80-2,14; p=0,28) and right ventricular dysfunction (OR, 1,23 (95% CI: 0,74-2,04; p=0,42).Conclusion. Thirty-seven percent of Russian patients with PE have AKI diagnosed by baseline creatinine. In 2/3 of the examined patients, stage 1 AKI is observed. The AKI incidence increases as the severity of PE increases. The presence of AKI reclassifies patients into a higher risk category for death and is associated with a significant increase in inhospital mortality.